(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
In this article I argue that Emergency Remote Teaching (ERT) has necessitated and produced some transformative teaching methods, using the frameworks of Freire and hooks. However, I argue, that their methods are incongruous with this moment of online learning because of the ‘invisibilisation’ of the marginalised and vulnerable students, who can and do easily disappear into the void of online learning. This makes dialogic teaching (Freire) and teaching in community (hooks) impossible. I use examples of two undergraduate history and history method (teaching history) classes, specifically looking at the teaching methods and the assessment methods. I draw thematically on what the students produced in their assessments, analysing their texts (poems, creative essays, artistic submissions), looking at how they engaged with the assignment (method) and what emerged in the assignment, reading specifically for political engagement. In this discussion, I look at both the possibilities and the limitations of online teaching. Ultimately, I argue, that the limitations outweigh the possibilities of online teaching, and that there is a danger in claiming victories or even good teaching standards in this context. The danger is that the students who disappear are written out of the script of the University, and the promises (however precarious) that post-university life in South Africa offers. My argument here, using two specific courses as evidence, is thus a contradiction and a balance: for exploring this portal, and everything it offers, but pushing back vehemently against complete online migration because, in a country as unequal as South Africa, it is unethical, unjust, and anti-critical pedagogy.